EFFECT OF FUNGAL TREATMENT ON RUMEN DEGRADABILITY AND CHEMICAL COMPOSITION OF POPULUS NIGRA SAWDUST AS LIGNOCELLULOSIC BIOMAS - F. Mirzaei Aghjehgheshlagh; M. Bayat; B. Darabighane; M. Sharari; J. Seifdavati1and B. Navidshad (Journal of Animal and Plant Sciences, 2018)
The present study was carried out to determine chemical composition and rumen degradability parameters of dry matter (DM), neutral detergent fiber (NDF), acid detergent fiber (ADF) ether extract (EE) and organic matter (OM) in Populus nigra sawdust biodegraded by Phanerochaete chrysosporium and Pleurotus ulmarius. The samples were incubated by the fungal biomass at 30 ˚C with 65 % relative humidity for 7 and 17 days and chemical composition of substrate was then analyzed. Using in situ technique enabled us to evaluate degradability of the samples in the rumen of two Moghani rams with rumen fistula. Significant differences were observed in DM, NDF, ADF, EE and ash contents as well as degradability parameters of DM, NDF, ADF and OM, including highly soluble and readily degradable fraction (a), insoluble and slowly degradable fraction (b), rate constant for degradation of the fraction b (c) and effective degradability (ED) in different times of biodegradation. The findings indicated that effects of white rot fungi on Populus nigra sawdust significantly decreased DM, NDF, ADF and OM while EE, ash content, DM and NDF degradability parameters were significantly increased.
Keywords: Phanerochaete chrysosporium; Pleurotus ulmarius; Chemical composition; Degradability; Populus nigra